Gender differences in mathematics : an integrative psychological approach - Gallagher, Ann M.; Kaufman, James C. (Cambridge University Press, 2005)
This book explores gender differences in math performance--and why males outperform females on high stakes standardized tests but not in the classroom. These differences are important because scores on such tests are generally used in decisions that have important consequences for students such as college admissions and job placement. The contributions in this volume present a variety of theories and research that help to explain the differences, and highlight the consequences. Illustratively, if females receive lower scores on the tests, they are likely to be exposed to fewer opportunities thereafter.